Comparação entre diferentes técnicas de moldagem utilizando transferentes específicos para implantes de hexágono interno: esquema all-on-4 - Silva, Lívia Amato Conceição Bueno da [UNESP] (2014)
The passive fit is one of the most important prerequisites in oral rehabilitation on implants with immediate loading and maintenance of osseointegration. Due to the importance of obtaining passivity in the success of prosthetic rehabilitation on implants, the failure of consensus on the techniques of molding and the absence of studies that evaluate the molding rehabilitation based on the concept All-on-4, the present study aims to analyze in vitro the accuracy of different methods of forming prosthetic rehabilitation in internal hexagon implant anatomical model installed in a metal jaw toothless. Variables in this study are the molding technique (Open, Closed and Index), transfer methods (conical transfer - no union and Intelligent square transfer), as well as methods of union of Intelligent square transfer (united Pattern resin sticks to prefabricated and joined together with metal sticks with cyanoacrylate resin and Pattern). After obtaining the molds (ExpressTM 3M/ESPE XT), forty models will be produced (4 groups; n=10) under mechanical vacuum mixing with type IV gypsum (Fuji-Rock EP). A metal structure fabricated on the master model with passive fit was screwed in the models obtained, on A analogue while measurements were made on analogs C and D and when screwed into analog D measurements were made in analogues A and B, by a program (Leica QWin) that received the images from a video camera coupled to a Leica (100X) loupe. There were significant differences in the comparisons between the techniques of molding and the master model, except for the Smart Square / Metal + Pattern (G2) with gap 65 μm, which behaved statistically similar to the master model group (60 μm). The Index group (G4) presented the less desadaptations (38 μm).